Preparation of Task Analysis For Making Sosis Sandwiches For Mild Mentally Disabled Students in Grade VII of Smplb at SLB Madhani In Garut Regency - Wahyuda, Nizar; Ratnawulan, Teti (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the task of making sausage sandwiches for mildly mentally disabled students in grade VII of SMPLB at SLB Madhani, Garut Regency. The aim is to support their life skills so that they become more structured and effective. The approach used is qualitative with a descriptive method, where data was obtained through direct observation in the classroom, in-depth interviews with key informants, documentation of learning activities, focus group discussions (FGD), and validation by experts. The findings of the study indicate that teachers have implemented various learning strategies, including demonstration (showing how to cook), direct instruction, drill (repeated practice), individualized instruction according to students' needs, and the use of special learning media such as videos, modules, and visual aids. Challenges encountered in the implementation of learning include limitations in supporting facilities and infrastructure, human resources, and limited learning time allocation. The results of this study are expected to contribute positively to the development of task analysis learning methods and strategies for students with mild intellectual disabilities, particularly at the Special Junior High School (SMPLB) level. In addition, this study can also be used as a reference for schools and the government in designing policies for providing more optimal facilities and training for educators and students with special needs.